1999
DOI: 10.1007/s004420050826
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and genetic variation in the haematocrit of fledgling pied flycatchers Ficedula hypoleuca

Abstract: We report a field study of the haematocrit of pied flycatcher (Ficedula hypoleuca) nestlings when close to fledging. First a descriptive study was conducted of both fledgling and adult haematocrit over 2 years to analyse correlates of variation in this trait. Then a swapping experiment was performed to see whether variation among fledglings had a measurable genetic component. Average fledgling haematocrits were lower than those of their male and female parents. Intraclass correlations among sibships in fledgli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
103
2

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(116 citation statements)
references
References 68 publications
5
103
2
Order By: Relevance
“…It could also be that haemoglobin concentration responds more to the factors acting on entire broods during the whole nestling stage, such as general trophic conditions and parasitic pressure in the nest, which would further explain higher intrabrood repeatability of this measure. Potti et al (1999) assessed within-brood repeatability of haematocrit in Pied Flycatcher nestlings and found it to be 0.7, which is similar to our result for haemoglobin.…”
Section: Discussionsupporting
confidence: 78%
“…It could also be that haemoglobin concentration responds more to the factors acting on entire broods during the whole nestling stage, such as general trophic conditions and parasitic pressure in the nest, which would further explain higher intrabrood repeatability of this measure. Potti et al (1999) assessed within-brood repeatability of haematocrit in Pied Flycatcher nestlings and found it to be 0.7, which is similar to our result for haemoglobin.…”
Section: Discussionsupporting
confidence: 78%
“…In nestling Pied Flycatchers (Ficedula hypoleuca) studied in our forest study site the repeatability of haemoglobin was assessed at 0.63 (Glądalski et al 2015a). Potti et al (1999) found that within-brood repeatability of haematocrit in Pied Flycatcher nestlings in Spain was 0.7. Our present long-term result for Blue Tits is high (0.68), which is consistent with previous findings.…”
Section: Discussionmentioning
confidence: 93%
“…The remaining nestlings were removed and transported in the same manner, and for the same length of time, as the translocated young, and then put back in their original nest to control for potential handling stress. All nests remained with the original number of young hatched, so that breeding chronology, breeding e¡ort of adults and intranest competition of nestlings were held constant (Potti et al 1999). Although we created broods where the same numbers of nestlings from two di¡erent families were raised together in the same nest, mortality resulted in unbalanced sample sizes.…”
Section: (A) Field Methodsmentioning
confidence: 99%
“…Genetic and environmental e¡ects on the concentrations of plasma carotenoids of o¡spring were estimated following a widely used approach (MerilÌ 1996;Potti et al 1999). This consists of a two-factor nested ANOVA where the main e¡ects were duplicate (a pair of nests matched by clutch size and hatching date) and nest of origin (nested within duplicates).…”
Section: (C) Statistical Analysesmentioning
confidence: 99%